If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14c + -6c = 0 Combine like terms: 14c + -6c = 8c 8c = 0 Solving 8c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '8'. c = 0 Simplifying c = 0
| -11+6+7n-9n=n+1 | | 4x-2(5x-8)=-56 | | (6x)=6(xy) | | 2m^2-7m-7m-13=-10 | | 5w-5+2(3w+7)=-5(w+1) | | 15u-8u=49 | | 6=4x/(12-x) | | X-2(-.3)=2 | | 13=5x+11 | | 3n+2=3 | | 3(2+2y)+4y=3 | | 7+4q=11+34 | | 6+6x=6(x-5) | | 7(x+4)=-2(5x-5)+2x | | (2x+1)-(-4x-9)= | | x+3x+6x=3450 | | 12(10)+3(14)=162 | | 9-x=x+12 | | 7-2n=4 | | 8(10)+3(14)=122 | | 4z-5=8x+3 | | -3(-2w+3)-9w=3(w-7)-3 | | 2y(y)=400 | | 2.1x-12.2= | | 481.194=13.4*6.3*w | | 3x-4+2x+10=21 | | -12/5=-6u | | -3(2x-4)=5x | | 3x+7-9+x=2x+3-x+4 | | -21=7/8y | | -6=-3/5w | | X+Y-3Z= |